A broad review on the usage of modular three-dimensional finite-difference groundwater flow model for estimating groundwater parameters - Shekhar S.; Jha M. (Institute for Ionics, 2022)
Modeling groundwater is a significant paradigm in hydrology application, which supports human life and agricultural land in a wide range. Thus, groundwater modeling is more helpful in the hydrological system. Moreover, the crucial part of groundwater modeling is artificial recharging, which helps estimate groundwater levels. Also, the process of the recharge system differs based on ground conditions. Besides, spatial representations are explained in a graphical structure to estimate groundwater mapping. Henceforth, the drawn graphical representation illustrates the ground condition with its density. Furthermore, the MODFLOW model is mostly utilized to design the graphic structure. Also, this present review has collected areas of ground-level data including Varanasi, West Bengal, South Korea, Africa, Jordan, Italy, and Beauraing. So, several existing works are discussed related to the Varanasi district. Finally, several chief parameters are discussed in tabular and graphical formats. Also, systematic future works are recommended in conclusion section. Thus, this review supports the researchers in discovering past difficulties and better solutions for the future.
This paper is submitted by the author of IIT (BHU), Varanasi ,India
Keywords: Groundwater parameters; Aquifer mapping; Artificial recharge; Groundwater; Modular three-dimensional finite